Abrupt Increase in ENSO Variability at 700 CE Triggered by Solar Activity. Issue 1 (23rd January 2023) - Jiang, Leilei; Yu, Kefu; Tao, Shichen; Li, Yueer; Wang, Shaopeng
Abstract: The El Niño–Southern Oscillation (ENSO) is the dominant interannual variability affecting global weather and climate. However, limited observational records hinder our understanding of the evolution of natural ENSO variability and its driving mechanisms. In this study, ENSO variations from 665 to 749 CE (Common Era) were investigated using monthly sea surface temperature (SST) records of the northern South China Sea derived from coral strontium to calcium ratios of sub‐fossil Porites obtained at the Xisha Islands. The results suggested the existence of cold conditions in this period relative to the twentieth century. No change in SST seasonality for the CE was found that is in agreement with the orbitally controlled insolation seasonality at that time. ENSO variability during 665–749 CE was enhanced by 39% than that during 1980–2014 CE and exhibited fluctuations. A persistent dampened ENSO variability with frequent El Niño events from 665 to 700 CE was followed by a rapid increase in variability to a level double that of the present. The frequency of La Niña events increased during this time. The abrupt transformation of ENSO activity at 700 CE was attributed to the increased natural radiative forcing induced by intense solar irradiance and weak volcanism. This paper demonstrates that ENSO variability can be influenced by external forcings, such as changes in solar and volcanic activity, and not only by the internal dynamics of the climate system. Plain Language Summary: Reconstructing the amplitude and frequency of historical El Niño and La Niña events will allow us to better understand the driving mechanisms of their evolution and improve predictions of ENSO under anthropogenic climate change. This study reconstructed monthly sea surface temperature (SST) from 665 to 749 CE using a continuous sub‐fossil coral Sr/Ca record from Xisha Islands. We demonstrated that the northern South China Sea and its adjacent area experienced cold conditions during this period, with no change in SST seasonality relative to the present. Our results also revealed that ENSO variability during 665–749 CE exhibited significant fluctuations from a state with dampened ENSO to one with amplified ENSO, accompanied by a transition from frequent El Niño to La Niña anomalies. The abrupt increase in ENSO variability after 700 CE was triggered by the increased solar irradiance and weak volcanic eruptions. This suggests that in addition to the internal dynamics of the climate system, ENSO variability is also influenced by external forcings. Key Points: Cooler conditions and similar sea surface temperature seasonality compared to the present characterized 665–749 CE El Niño–Southern Oscillation (ENSO) variability during 665–749 CE was 39% higher than that during 1980–2014 CE Enhanced solar activity triggered an abrupt increase in ENSO variability at 700 CE